Sexual dysfunction in women with type 2 diabetes mellitus: A single-centre cross-sectional study from Bangladesh - A. B. M. Kamrul-Hasan; Muhammad Shah Alam; Nusrat Zarin; Fatema Tuz Zahura Aalpona; Marufa Mustari; Farhana Akter; Nadia Jannat; Umme Azad; Palash Kumar Chanda; Abdur Rafi; Mohammad Jahid Hasan; Shahjada Selim (Archives of Endocrinology and Metabolism, 2023)
ABSTRACT Objective: Sexual dysfunction among women with diabetes is a common but neglected health issue worldwide. The objective of the present study was to investigate the prevalence of sexual dysfunction and its associated factors among women with type 2 diabetes mellitus (T2DM). Subjects and methods: This cross-sectional comparative study comprises 150 women with diabetes and 100 healthy women without diabetes who visited the endocrinology outpatient department of Mymensingh Medical College Hospital (MMCH). The data were collected from July to December 2019. Sexual dysfunction was assessed by the 19-item Female Sexual Function Index (FSFI). Informed consent was obtained before participation. Collected data were analysed by SPSS 26. Results: More women with diabetes than control subjects reported sexual dysfunction (79% vs. 72%; p = 0.864). The global FSFI score was lower among the diabetes patients than among the healthy controls (20.8 ± 7.2 vs. 23.7 ± 4.8; p < 0.001). Patients with T2DM scored significantly lower in the domains of desire (p = 0.04), lubrication (p = 0.01), orgasm (p = 0.01), and satisfaction (p < 0.001), but not the domain of arousal (p = 0.09). A prolonged duration of diabetes was the primary contributor to orgasm problems (adjusted odds ratio, aOR 1.3, 95% CI 1.1-1.7) and painful intercourse (aOR 1.2, 95% CI 1.1-1.5). Conclusion: Sexual problems are frequent in women with diabetes. Inclusion of sexual health in comprehensive diabetes management is crucial to address this problem as well as to improve the quality of life of female diabetes patients.